Oxidative stress response and its role in sensitivity to isoniazid in mycobacteria: characterization and inducibility of ahpC by peroxides in Mycobacterium smegmatis and lack of expression in M. aurum and M. tuberculosis. - Dhandayuthapani, S (1996)
Mycobacterium tuberculosis is a natural mutant with inactivated oxidative stress regulatory gene oxyR. This characteristic has been linked to the exquisite sensitivity of M. tuberculosis to isonicotinic acid hydrazide (INH). In the majority of mycobacteria tested, including M. tuberculosis, oxyR is divergently transcribed from ahpC, a gene encoding a homolog of the subunit of alkyl hydroperoxide reductase that carries out substrate peroxide reduction. Here we compared ahpC expression in Mycobacterium smegmatis, a mycobacterium less sensitive to INH, with that in two highly INH sensitive species, M. tuberculosis and Mycobacterium aurum. The ahpC gene of M. smegmatis was cloned and characterized, and the 5' ends of ahpC mRNA were mapped by S1 nuclease protection analysis. M. smegmatis AhpC and eight other polypeptides were inducible by exposure to H2O2 or organic peroxides, as determined by metabolic labeling and Western blot (immunoblot) analysis. In contrast, M. aurum displayed differential induction of only one 18-kDa polypeptide when exposed to organic peroxides. AhpC could not be detected in this organism by immunological means. AhpC was also below detection levels in M. tuberculosis H37Rv. These observations are consistent with the interpretation that ahpC expression and INH sensitivity are inversely correlated in the mycobacterial species tested. In further support of this conclusion, the presence of plasmid-borne ahpC reduced M. smegmatis susceptibility to INH. Interestingly, mutations in the intergenic region between oxyR and ahpC were identified and increased ahpC expression observed in deltakatG M. tuberculosis and Mycobacterium bovis INH(r) strains. We propose that mutations activating ahpC expression may contribute to the emergence of INH(r) strains.